Disposable-soma senescence mediated by sexual selection in an ungulate - Carranza, Juan; Alarcos, Susana; Sánchez-Prieto, Cristina B.; Valencia-Ruíz, Juliána; Mateos, Concha (My University, 2004)
Senescence may result from an optimal balance between current reproductive investment and bodily repair processes required for future reproduction1, a theoretical prediction difficult to prove especially in large, long-lived animals. Here we propose that teeth that have fixed dimensions early in life, but that wear during chewing, can be taken as a measure of total lifetime ‘repair’, and their wear rate as a measure of current expenditure in performance. Our approach also considers the sexual selection process to investigate the advance of senescence in males compared with females, when selection favouring competition over mates reduces the reproductive lifespan of males2. We studied carcasses of 2,141 male and 739 female red deer (Cervus elaphus) of different ages, finding that male molariform teeth emerged at a far smaller size than expected from body size dimorphism. This led to higher workload, steeper wear rate and earlier depletion of male teeth than in females, in concordance with sex-specific patterns of lifetime performance and reproduction. These findings provide the empirical support for the disposable-soma hypothesis of senescence3, which predicts that investment in bodily repair will decrease when the return from this investment may not be realized as a result of other causes that limit survival or reproduction.
Keywords: Ungulados - Envejecimiento; Senescence; sexual selection; ungulate